Archery and target-shooting in pre-Islamic Java; What can be known? - Jákl, JiŘí (Wacana, Journal of the Humanities of Indonesia, 2025)
In Java today, archery survives as a traditional discipline called jemparingan. Javanese archery involves targeting a pendulum-like target from a shooting distance of 35 to 50 metres. The archers take aim from a cross-legged seated posture (bersila) and typically wear traditional Javanese attire during competitions. Though archery has been practiced in Java for long time, there has been surprisingly little effort to study its rich history. This study aims to historicize the jemparingan by looking at the Old Javanese archery terminology and the origin of competitive (“contest”) archery in Indonesia. The evidence from pre-Islamic Java, textual, visual, and archaeological, demonstrates that Javanese jemparingan is rooted in a much older tradition of precision shooting (target shooting), which can be traced to pre-Islamic times. I propose that shooting at targets in the form of a wooden or metal split-drum (kukulan) was known in Java as a form of military training by Majapahit times in the fourteenth century CE. The origin of this practice is probably rooted in the introduction of more powerful and hence more precise bows, via the Mongol and Chinese influences during the invasion of Java in 1292 CE or shortly after this historical event.